Molecular epidemiology study of programmed death ligand 1 and ligand 2 protein expression assessed by immunohistochemistry in extensive-stage small-cell lung cancer - Steiniche, Torben; Georgsen, Jeanette Baehr; Meldgaard, Peter; Deitz, Anne C.; Ayers, Mark; Pietanza, M. Catherine; Zu, Ke (Frontiers in Oncology, 2024)
Objectives: Prevalence of tumor PD-L1 expression in extensive-stage small-cell lung cancer (ES-SCLC) is variable, and data on PD-L2 expression are limited. The prognostic values of these biomarkers are not well understood. The current study was conducted to address these data gaps.A retrospective cohort study of Danish patients with histologically confirmed ES-SCLC and evaluable tumor samples who were receiving usual care before the introduction of immunotherapy was conducted. Protein expression of PD-L1 and PD-L2 was determined by immunohistochemistry (IHC) using the PD-L1 IHC 22C3 pharmDx assay and a PD-L2 IHC assay using a propriety mouse monoclonal antibody. A combined positive score (CPS) of ≥1 was used to define biomarker positivity. Kaplan-Meier plots and Cox proportional hazard models were employed to assess the relationship between PD-L1 and PD-L2 protein expression and OS.Results: Among 80 patients, 31% (n=25) and 36% (n=29) had disease positive for PD-L1 and PD-L2, respectively. Overall, 85% (n=68) of patients had concordant PD-L1/PD-L2 status; 26% (n=21) had double positive disease (both PD-L1 and PD-L2 CPS ≥1) and 59% (n=47) had double negative disease (both PD-L1 and PD-L2 CPS <1). PD-L1 and PD-L2 positivity were each associated with longer OS (unadjusted hazard ratios [HRs], 0.35 [95% CI, 0.21−0.61] and 0.50 [95% CI, 0.31−0.82]); the associations persisted after adjustment for several known prognostic factors (HRs, 0.41 [95% CI, 0.22-0.75] and 0.44 [95% CI, 0.25-0.79] for PD-L1 and PD-L2 positivity, respectively). When evaluating OS in patients with double positive disease, unadjusted and adjusted HRs for double positive compared with double negative were similar to those with only PD-L1 or PD-L2 positivity (unadjusted HR, 0.36 [95% CI, 0.20-0.64]; adjusted HR, 0.36 [0.18-0.73]). Conclusion: PD-L1 and PD-L2 positivity were observed in approximately one-third of assessed ES-SCLC tumor samples and were highly congruent. Patients with PD-L1 and PD-L2 positivity, alone or combined, were associated with longer OS, independent of other prognostic factors.